Coaching-Based Academic Supervision as A Means of Strengthening Citizenship Values for Elementary School Teachers - Mulyati Bangi; Zulaecha Ngiu; Muchtar Ahmad (International Journal of Education, Vocational and Social Science, 2025)
The objectives of this study are 1. To analyze the implementation of coaching-based academic supervision for elementary school teachers in Telaga District, including strategies, methods, and challenges faced in its implementation, 2. To identify the impact of coaching-based academic supervision on strengthening elementary school teachers' citizenship attitudes, such as attitudes of understanding rights and obligations, responsibility, and empathy, 3. To explore the experiences and perceptions of teachers and principals regarding the effectiveness of coaching-based academic supervision in improving professionalism and internalization of citizenship values. 4. To prepare strategic recommendations for optimizing coaching-based academic supervision as a sustainable coaching model in order to strengthen teachers' citizenship attitudes in elementary school environments. This study uses a qualitative method. Data collection was carried out through interviews, observations and documentation. The subjects of this study were principals and teachers. The results of the study indicate that the implementation of coaching-based academic supervision in Telaga District has been running effectively with a collaborative and participatory approach. The principal acts as a mentor who encourages teachers to develop through constructive reflection and feedback. This supervision is integrated with the learning community (CUSTOM) which strengthens the culture of professionalism and mutual learning. Between teachers. In addition, coaching-based supervision has a positive impact on teachers' citizenship attitudes. Teachers become more reflective in their role as character educators, and more aware of integrating citizenship values ​​such as tolerance, mutual cooperation, and responsibility in learning. This strengthens the role of teachers as agents of instilling Pancasila values ​​in elementary schools